Intercambiador de transportes (2017)
My project is a transport hub that seeks to complement the proposed metro station for 72 street with Caracas Avenue in the city of Bogotá.The project propose different services for the different means of transport, such as parking for cars, bicycles and motorcycles; car workshops, taxi stand, and access to the metro line.